Widowhood and Health Status Among Chinese Older Adults: The Mediation Effects of Different Types of Support - Guo, Yu; Ge, Tingshuai; Mei, Li; Wang, Lina; Li, Jingbo (Frontiers in Public Health, 2021)
Although many studies have suggested that widowhood is related to worse health conditions among older adults, few have examined the mediation effects of social support between widowhood and health. Employing mediation analysis to a sample of data from the 2014 wave of China Longitudinal Aging Social Survey (CLASS), this study examined the mediation effects of social support, including emotional support, instrumental support, and companionship, in the widowhood-health association among older adults. The results indicated that the negative effect of widowhood on older adults' health was in part attributable to decreased emotional support and companionship. Specifically, emotional support exerted a significant role in the widowhood-mental health association, and companionship exerted a significant role in widowhood-physical health and widowhood-mental health associations. In the subsample analysis, the mediation effects were only significant among female older adults, and among rural older adults. Our findings highlight the importance of emotional support and companionship in maintaining health among widowed older adults and strategies should pay more attention to female and rural widowed older adults.